Порівняльний аналіз ЄС та України в питаннях захисту прав інтелектуальної власності - Гаряєва, Ганна Михайлівна; Домінов, М. Е. (НТУ "ХПІ", 2017)
У статті досліджуються основні розбіжності в питаннях захисту інтелектуальної власності України та ЄС. Автор проводить порівняльний аналіз нормативно-правових документів чинного законодавства України та ЄС у сфері охорони об’єктів промислової власності, так і системи патентної охорони. Що дає підстави стверджувати, що деякі положення різняться. У статті розкрита ця неузгодженість і виявлені питання щодо нормативного вдосконалення положень законодавства стосовно захисту ІВ у відповідність до норм законодавства ЄС. Що сьогодні є особливо актуальним.

The article deals with the main differences in protecting the intellectual property between Ukraine and EU. The author analyzes legal documents from the current constitution of Ukraine and EU in protecting objects related with intellectual property and the system of protecting patents. What gives reason to believe that some directions are different. It happens due to not perfect modern regularly support of the intellectual property. The article reveals in consistencies and found issues of regulatory to improve the legislation on the protection of IP in compliance with the EU legislation. What is especially important today. The main focus is on the fact that if Ukraine wants to enter the EU, as a competitive country, it should have an effective system of protecting the intellectual property.
Comparative analysis of the EU and Ukraine in the protection of intellectual property rights
Keywords: система патентної охорони; конкурентоспроможність; недобросовісна конкуренція; Директива ЄС; промислові зразки; competitiveness; unfair competition; industrial prototypes